Region Variation of Hematological Malignancies and Solid Tumors in Children in East Java - Andi Cahyadi; Maria Christina Shanty Larasati; Mia Ratwita Andarsini; I Dewa Gede Ugrasena; Esthy Poespitaningtyas; Diah Kusuma Arumsari (Asian Journal of Health Research, 2023)
Introduction: The prevalence of childhood cancer in East Java is unevenly associated with differences in exposure to carcinogens in urban-industrial areas, agricultural chemicals, industrial waste along the river, and socio-culture. However, there are no data on regional variations in childhood cancer in East Java. We describe the regional variation of hematological malignancies and solid tumors in East Java. Material and Methods: The study was conducted by cross-sectional on children with cancer aged <18 years in dr. Soetomo General Academic Hospital in 2014-2015. The data evaluated were gender, age, and cancer type (hematological malignancy and solid tumor). They came from Mataraman, Madura Island, industrial-urban areas (Surabaya-Sidoarjo-Gresik), and Tapal Kuda. We used the Chi-square test and Logistic Regression for data analysis (p<0.05 for two-tailed test). Results: During the study period, there were 353 children with cancer, consisting of 56.9% hematological malignancies and 43.1% solid tumors: 60.9% boys, and 82.4% aged <10 years. Hematological malignancies in industries-urban areas are more numerous than in Mataraman, Madura Island, and Tapal Kuda; 67.8%, 52.8%, 47.2%, and 50.9%, respectively (p=0.031). Hematologic malignancies were also more common in aged <10 years (60.5% vs 40.3%; p=0.004 OR=2.265; 95% CI=1.295-3.362) and Javanese race (p=0.025; OR=3.257; 95% CI=1.121-5.263). Children in industrial-urban areas had more hematological malignancies than Mataraman (p=0.027; OR=2.353; 95% CI=1.101-5.030) also Tapal Kuda (p=0.015; OR=1.881; 95% CI=1.132-3.124) and Madura Island (p=0.032; OR=2.033; 95% CI=1.064-3.882). Conclusion: Hematological malignancies in industry and urban areas are more numerous than Mataraman, Madura Island, and Tapal Kuda area. Solid tumors were mostly found on Madura Island.